(untitled) (Doctor Virtualis, 2025)
In his Collationes (ca. 1136), Peter Abelard entrusts to the philosopher two severe criticisms concerning first the impressive bulk of decretals uninterruptedly issued by the popes and secondarily the custom of conceding dispensations that – he assumes – make lecit what before was illegal and viceversa, so infringing the lex naturae. If the first argument is understable and really documented, is more difficult to explain the second one. One can suppose that it was suggested by Abelard’s indignation against the expulsion of Eloisa and her sisters away from the monastery of Argenteuil, declared by the synod of St. Germain-des-Prés (1129). A decision inspired and directed by Suger, powerful abbot of St. Denis, seemingly relying on documents probably false, nevertheless credited by the members of the religious assembly, so neglecting the ordinary canon law that granted, by time, the good reasons of the nuns.